Charisma and Spiritual Practices of Abah Guru Sekumpul (1942–2005): A Historical Study from South Kalimantan - M Kautsar Thariq Syah; Putri Lailatus Sa'adah; Mohammad Dindin Hamam Sidik (CV. FOUNDAE, 2025)
KH Muhammad Zaini Abdul Ghani Al-Banjari, known as Abah Guru Sekumpul (1942–2005), was a highly revered Islamic scholar and spiritual figure in South Kalimantan. As the eighth descendant of Maulana Syekh Muhammad Arsyad Al-Banjari, he was known for his piety, humility, generosity, and dedication to religious teachings. This study aims to explore the spiritual legacy and character of Abah Guru Sekumpul, focusing on his personal virtues, spiritual practices, and reported karomah (miracles). A qualitative library research method was employed, involving the collection and analysis of primary and secondary sources. Findings highlight his emphasis on sincerity in seeking knowledge, the spiritual benefits of devotional practices, and his unique connection with spiritual figures, both in life and after death. One remarkable incident occurred when, despite severe illness, he appeared healthy to lead a religious gathering—demonstrating what is believed to be a manifestation of karomah. The study concludes that Abah Guru Sekumpul's influence endures through his teachings and the reverence of his followers, exemplifying the traits of a waliyullah (saint).